O protocolo de Kyoto e o mecanismo de desenvolvimento limpo: Uma avaliação de suas possibilidades e limites. - Godoy, Sara Gurfinkel Marques de (2005)
The purpose of this work is to present the limits and benefits of Clean Development Mechanism (CDM) Projects implementation. The supplemental objectives are the limits and potentialities evaluation of the Kyoto Protocol and the Tools for the Demonstration and Assessment of Additionality analysis, that is an tool proposed by CDM Executive Committee enabling the companies who propose the CDM projects to prove the additionality of its projects. The Protocol firmed in 1997 during COP 3 (3rd Conference of Parts) of United Nations Framework Convention on Climate Change (UNFCCC), in Kyoto, determined emissions ceiling for some developed countries, considering an institucional apparatus to provide support to the process implementation. In order to make flexible the goals fullfilment, the Protocol creates mechanisms (the Mechanism of Clean Development, the Joint Implementation and the Emissions Trade) that also allow the fullfilment of the reduction objectives. The countries can reach its reduction goals, purchasing emission reduction from other countries. Therefore, these tools enable and improve the carbon market. As relevant part of this work, the CDM appears as a great tool that if well used, can bring benefits for development countries, bringing up economic and enviromental advantages once these projects are implemented in its territories, promoting the sustainable development. There are still plenty of challenges ahead for the CDM and the Protocol development, as reduce the uncertainties of regulatory framework, minors transaction costs and institutional improvements that can be reached. Related to the Tools for the Demonstration and Assessment of Additionality, it fullfils with its function to demonstrate adittionnality, not limiting or promoting new CDM projects